Catalytic enantio- and diastereoselective alkylations with cyclic sulfamidates. - Moss, T; Alonso, B; Fenwick, DR; Dixon, D (2010)
(Figure Presented) Open for business: The enantio- and diastereoselective nucleophilic ring opening of five-membered and six-membered cyclic sulfamidates under asymmetric phase-transfer catalysis is presented. A range of pro-nucleophiles have been successfully alkylated in good yields and in good to excellent enantioselectivites. © 2010 Wiley-VCH Verlag GmbH and Co. KGaA.